Pengaruh Kecintaan Siswa Pada Al-Qur’an Terhadap Perilaku Sosial di Sekolah Dasar Al Islam Plus Kabupaten Sidoarjo - Benny Angga Permadi (Attadrib: Jurnal Pendidikan Guru Madrasah Ibtidaiyah, 2021)
Students nowadays are reluctant to go to the mosque to learn Quran. Their characters are influenced by technology such as television, the internet, and video game which then make parents and teachers worried and anxious if they will act negatively. This thesis uses research design of mixed-method with the objective to complete the image of research result about the phenomenon and to strengthen the analysis. The research strategy is done by combining the data from observation, interviews, and questionnaires in order to get qualitative and quantitative data. The data analysis is continuous qualitative-quantitative analysis, it is done by analyzing qualitative data and followed by analyzing the data through quantitative one. The hypothesis testing is done by using simple linear regression analysis with SPSS 18 program. The result of qualitative data is the students’ affection on Quran in Islamic Elementary School through Quran memorizing a program. Students’ social behavior is positive, whether toward friends and teachers in school. The result of quantitative data shows that students affection on Quran is 44% categorized as high, 40% as fair, and 16% as low. Students’ social behaviour shows that 74% as high, 10% as fair and 16% as low. The hypothesis testing uses t-test and the result of tcount is 6.356 with the significance of 0.026. The tcount ? ttable (6.356 ? 2.010) or sig. t ? 5% (0.026 ? 0.05), it can be concluded that the variable of students’ affection on Quran has significant influence toward the variable of students’ social behaviour. The students’ social behavior is influenced by 55% of a variable of students’ affection on Quran while 45% is influenced by other variables outside this research